Work-Life Factors and Job Satisfaction among Music Therapy Educators: A National Survey. Issue 1 (1st September 2017) - Gooding, Lori F
Abstract: Work-life factors are individual, organizational, and societal factors that influence work-life success and balance. Faculty members' perceptions of these factors have been shown to influence job satisfaction, and scholars have suggested that faculty work-life quality and satisfaction has declined in recent years. Trends in work-life satisfaction and balance have been studied for decades, but little is known about the work-life and job satisfaction of music therapy educators. The purpose of this study was to identify specific work-life factors of music therapy faculty in the United States and explore faculty members' perceptions of these factors. A survey link was sent out, and 100 music therapy educators returned surveys (37% response rate). Eighty-nine provided usable responses. Results indicated that music therapy faculty are predominantly female and white, with an average age of 49. Two-thirds were tenured/tenure- track, and the majority worked 41 or more hours per week. Average credits taught per semester were 9.19, which included both traditional and clinical course formats. Other job duties included service, advising, and research. Salary data were mixed in comparison to other music faculty. Most respondents were somewhat or very satisfied with their current position (85.71%), but a substantial portion of respondents were somewhat or very dissatisfied with salary (41.61%), work-life balance (39.29%), and workload (35.72%), with a substantial proportion stating that their workload was higher than other music and non-music faculty. More research is needed to ensure adequate support of future music therapy faculty.